Predicting Volatility of Non-Performing Financing: Lessons from Indonesian Islamic Banking Industry - Mubarok, Faizul; Hamid, Abdul; Al Arif, Mohammad Nur Rianto (IAIN Salatiga, 2020)
Islamic banking financing is carried out into three categories, namely financing based on economic sectors, financing based on contracts, and financing based on types of use. The funding is faced with risks where the customer is unable to pay the loan. This study discusses the forecasting of Islamic banking problem financing in Indonesia using monthly data from 2003 to 2019. Prediction is made using the Autoregressive Conditional Heteroscedasticity-Generalized Autoregressive Conditional Heteroscedasticity (ARCH-GARCH) method. Forecasting from the results of this study shows that non-performing financing tends to decrease in Indonesia. Islamic banking has been able to manage problem financing well. Islamic banking financing should be focused on sectors that have low risk. The results of this study are undoubtedly useful for stakeholders to make policies to improve the quality of the funding.